ATRT-10. SPATIO-TEMPORAL DELETION OF SMARCB1 DETERMINES MOUSE AT/RT SUBTYPES. Issue 2 (22nd June 2018) - Han, Zhi-Yan; Andrianteranagna, Mamy; Tauziède-Espariat, Arnault; Fréneaux, Paul; Masliah-Planchon, Julien; Bourneix, Christine; Pierron, Gaelle; Leruste, Amaury; Chauvin, Céline; Varlet, Pascale; Surdez, Didier; Delattre, Olivier; et al.
Abstract: The cell(s) of origin of AT/RTs remains unclear. We previously developed a mouse model consisting in tamoxifen inducible system in a Smarcb1 Flox/Flox ;Rosa26-Cre ERT2 background. We obtained two subgroups of intracranial tumors, one with neuronal and the other with non-neuronal features, in keeping with the diversity observed in human AT/RTs. To investigate the potential cell(s) of origin of those various AT/RTs, we first endeavored to specify whether different time points of Smarcb1 inactivation correlated with specific anatomic location and/or molecular subgroups. Thereby, we identified that the neuronal group, mostly developing from the sub-ventricular zone and the spinal cord, was almost exclusively obtained with the earliest inactivation time point(E6-E7). In contrary, the non-neuronal group emerged after Smarcb1 inactivation at any time point(E6-E10), and showed intracranial but extra-parenchyma/meningeal origins. In order to more specifically identify the cell(s) of origin for the neuronal group, we next generated developmental stage-specific conditional knockout mice carrying Smarcb1 inactivation by restricting Cre expression upon promoters characteristic for various neural stem cells/progenitors. While Smarcb1 Flox/Flox ;Atoh1Cre ERT2 showed ataxia but failed to give rise to any tumor whatever the embryonal time point, targeting Nestin-expressing cells led to tumors with morphological rhabdoid features; these again showed some molecular diversity as observed in human AT/RTs. The study of the impact of Smarcb1 inactivation in other promoter-restricted backgrounds is ongoing. In conclusion, we show that spatio-temporal deletion of Smarcb1 determines mouse AT/RT subtypes. Our new mouse models not only give insight on the cell(s) of origin, but also provide interesting preclinical models.